Dampak Penerapan Pembelajaran Fikih terhadap Kedisiplinan Shalat Siswa Madrasah Tsanawiyah - Luluk Fatimah (Jurnal Manajemen dan Pendidikan Agama Islam, 2024)
This study aims to describe the impact of the implementation of Fiqh learning on students' prayer discipline at MTs Darul Ulum. Fiqh learning in madrasahs aims to guide students in recognizing, understanding, and practicing Islamic law in everyday life. The method used in this study is qualitative with a descriptive design. Data were collected through interviews, observations, and documentation. The validity of the data was tested by extending observations, increasing the accuracy of the research, as well as data triangulation and the use of relevant references. Data were analyzed through the stages of data collection, data reduction, data presentation, and verification of conclusions. The results showed that the implementation of Fiqh learning had a positive effect on increasing the discipline of Dzuhur prayer worship for grade VII students at MTs Darul Ulum. Students can get used to performing obligatory prayers according to the teachings of the Fiqh teacher, with the development of increasing academic values, especially in the Fiqh subject, and showing an attitude of responsibility and obedience in performing obligatory prayers.